Epigenetics in Neurodegenerative Diseases: The Role of Histone Deacetylases - Sharma, Sorabh; Sarathlal, K.C.; Taliyan, Rajeev (CNS & Neurological Disorders - Drug Targets, 2019)
Background & Objective: Imbalance in histone acetylation levels and consequently the dysfunction in transcription are associated with a wide variety of neurodegenerative diseases. Histone proteins acetylation and deacetylation is carried out by two opposite acting enzymes, histone acetyltransferases and histone deacetylases (HDACs), respectively. In-vitro and in-vivo animal models of neurodegenerative diseases and post mortem brains of patients have been reported overexpressed level of HDACs. In recent past numerous studies have indicated that HDAC inhibitors (HDACIs) might be a promising class of therapeutic agents for treating these devastating diseases. HDACs being a part of repressive complexes, the outcome of their inhibition has been attributed to enhanced gene expression due to heightened histone acetylation. Beneficial effects of HDACIs has been explored both in preclinical and clinical studies of these diseases. Thus, their screening as future therapeutics for neurodegenerative diseases has been widely explored. Conclusion: In this review, we focus on the putative role of HDACs in neurodegeneration and further discuss their potential as a new therapeutic avenue for treating neurodegenerative diseases.
Keywords: Parkinson' s disease